Sex-Specific Differences in Outcomes Following Thyroidectomy: A Population-Based Cohort Study. Issue 6 (30th November 2021) - Gut, Lara; Bernet, Selina; Huembelin, Monika; Mueller, Magdalena; Baechli, Ciril; Koch, Daniel; Nebiker, Christian; Schuetz, Philipp; Mueller, Beat; Christ, Emanuel; Ebrahimi, Fahim; Kutz, Alexander
Abstract : Introduction: Numbers of thyroidectomies and awareness of postoperative quality measures have both increased. Potential sex-specific variations in clinical outcomes of patients undergoing thyroidectomy are controversial. Objective: The aim of this study was to investigate sex-specific differences in outcomes following thyroidectomy. Methods: This is a population-based cohort study of all adult patients undergoing either hemi- or total thyroidectomy in Switzerland from 2011 to 2015. The primary outcome was all-cause 30-day readmission rate. The main secondary outcomes were intensive care unit (ICU) admission, surgical re-intervention, in-hospital mortality, length of hospital stay (LOS), postoperative calcium disorder, vocal cord paresis, and hematoma. Results: Of 16, 776 patients undergoing thyroidectomy, the majority of patients undergoing thyroidectomy were female (79%), with a median age of 52 (IQR 42–64) years. Within 30 days after the surgery, male patients had significantly higher rates of hospital readmission (adjusted risk ratio [RR] 1.38; 95% confidence interval [95% CI] 1.11–1.72, p = 0.008) and higher risks for postoperative ICU admission (RR 1.25; 95% CI, 1.09–1.44, p = 0.003) than female patients. There were no significant differences among sexes in the LOS, rates of surgical re-interventions, or in-hospital mortality. While postoperative calcium disorders due to hypoparathyroidism were less prevalent among male patients (RR 0.63; 95% CI, 0.54–0.72, p < 0.001), a 2-fold higher incidence rate of postoperative hematoma was observed (RR 1.93, 95% CI, 1.51–2.46, p < 0.001). Conclusions: Male patients undergoing thyroidectomy have higher 30-day hospital readmission and ICU admission rates. Following surgery, male patients revealed higher rates of neck hematoma, while hypocalcemia was more frequent among female patients.